(untitled) (Salduie, 2025)
This paper aims to present a gnomon or sundial discovered in 2020 at the Roman villa of the "Pompeu/Pompeii" or Can Ring, located in the municipality of Besalú (Girona, Catalonia). The focus of the work is not only to describe and characterise the piece, but also to explore, to the extent possible, aspects such as its manufacture, the material used (local travertine), its typology, the possible makers, its location within the villa, its possible functions, and its significance. Part of the interest lies in the scarcity of sundials in Hispania, with less than forty known and published examples to date.